Development of Alternating Current and Voltage E-Book Based on Blender Software to Improve Students Critical Abilities in Senior High School - Arfa, Trirahma Novalia Putri; Dwandaru, Wipsar Sunu Brams (Kasuari: Physics Education Journal (KPEJ), 2025)
This study aims to: (1) produce a physics e-book based on blender software that is suitable for use in schools, (2) determine the practicality of a physics e-book based on blender software for teachers and students of class XII MIPA in the learning process, (3) determine the effectiveness of a physics e-book based on blender software to improve critical thinking skills. This study uses the ADDIE model. In the analysis stage, researchers conducted observations, interviews, and distributed questionnaires to teachers and students of class XII MIPA SMAN 2 Sabang; the design stage designed the e-book grid, animation of alternating current and voltage based on blender software, compiled teaching modules, and test instruments; the development stage obtained the results of the e-book draft, teaching modules, data analysis techniques used in the development stage, namely V'Aiken and feasibility. The implementation stage used a pretest-posttest control group design. The evaluate stage tested the data generated. The results showed that: (1) the e-book based on the assessment of expert lecturers, teachers and colleagues is very feasible to be used in physics learning based on the results of the assessment of media feasibility and material feasibility, obtaining an average score of 94.55% and 92.37% with a very feasible category; (2) The e-book is very practical to use based on the practicality response questionnaire of teachers and students which obtained an average score of 97.67% and 92.48% with a very practical category; (3) The e-book is effective in improving critical thinking skills in the experimental class with a gain of 0.6.